2021
DOI: 10.1002/er.6958
|View full text |Cite
|
Sign up to set email alerts
|

Application of microfluidic paper‐based analytical device (μPAD) to detect COVID‐19 in energy deprived countries

Abstract: Coronavirus disease has spread all across the world. Low-and medium-income countries are more affected economically and socially compared to developed countries due to the lack of a rapid, robust, and affordable testing infrastructure. Furthermore, the high cost of real-time polymerase chain reaction (PCR) system, sophisticated user-handling procedure, and high expense of the conventional clinical tests are the root causes of the less accessibility of the testing systems to the users. In this study, a COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…A µPAD device coupled to LAMP amplification has been hypothesized for the detection of SARS-CoV-2 using wax barriers to separate the individual chambers of the µPAD device. These chambers consist of a sample zone, buffer zone, LAMP master mix zone, mixing zone and finally a sensor zone [ 101 ]. Similar cost-effective and simple approaches could be applied to the detection of arboviral infection in POC applications.…”
Section: Point Of Care Diagnosticsmentioning
confidence: 99%
“…A µPAD device coupled to LAMP amplification has been hypothesized for the detection of SARS-CoV-2 using wax barriers to separate the individual chambers of the µPAD device. These chambers consist of a sample zone, buffer zone, LAMP master mix zone, mixing zone and finally a sensor zone [ 101 ]. Similar cost-effective and simple approaches could be applied to the detection of arboviral infection in POC applications.…”
Section: Point Of Care Diagnosticsmentioning
confidence: 99%
“…These sensors proved to be effective due to their high sensitivity, enabling accurate detection of the viruses [95,96]. Although paper-based sensors have high sensitivity, there are challenges such as regular standardization and approval for clinical use [97,98].…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…Paper-based microfluidics have been explored that are inexpensive to fabricate, but limited to the resolution of the printers used [14]. However, paper-based microfluidics has shown promising results for low-resource settings [15,16]. Recently stereolithography (SLA) based 3D printing (3DP) of microfluidic channels have been demonstrated that provided a new inexpensive alternative to LOC silicon microfabrication techniques [17][18][19].…”
Section: Introductionmentioning
confidence: 99%